Parental treatment styles and their relationship to psychological adjustment among fourth year primary students - CHETTOUH, Bakhta (Social Sciences Journal)
This study aims to reveal the nature of the relationship between parental transaction methods (mother/father), and its relation with the psychological compatibility of students of forth year primary school, in addition to the recognition of the differences between the sample members in both variables according to the sex and parents educational level within the Descriptive Correlative Approach. This study relies on a sample of (140) pupil of forth year primary school in Laghouat. 69 of them are males and 71 are females their ages are between (9 and 11). We used two measures: parental Treatment methods (the mother/the father), (Anafiai, 1992), and the Psychological compatibility (Chkir ,2003), we rely also on the Statistical package of sociology , in extracting the arithmetic averages , the standards deviations , the link transactions , examination(s) , and the analysis of mono – variance . The study concluded that there is no linked relationship of the treatment methods and its dimensions, and the total degree of the psychological integration. The study concluded also that there are no يعهح انؼهٕو االظرًاػٙج انؼذد 27َٕ فًثش2017 141 differences between males and females in the degree of parental treatment methods (the father/the mother), and in the psychological integration and its dimensions. It brought out that there are no differences between the parental treatment methods with its dimensions, and the psychological integration with educational level of parent. According to the results of this study we raise alert to the ears of parents that it a must to practice positive treatment methods due its influence on the psychological integration. Also it is must to establish Guidance and guidance centers which guide both parents and their children to solve the problems correctly and wisely. In addition to raising the awareness and interest toward the correct parental treatment methods through different media means, and its positives toward pupils integration .inside and outside the school